PENGARUH FASILITAS FISIK TERHADAP KEPUTUSAN PEMBELIAN KAMAR TAMU DI THE AXANA HOTEL PADANG - Jabbar, Abdul (RC-INSTITUT, 2019)
The study and was initiated by the decline in occupancy rate the guest room in the period of 2016-2017. This study aims to : (1), knowing the physical in the Axana the Padang, (2), knowing the purchasing decision of the room at The Axana the Padang, and (3) Analyze the influence of the physical against the decision of the purchase of the guests at The Axana the Padang. This type of research is sort of descriptive set of quantitative. The maker of samples is purposive sampling as many as 88 people. The gathering data using the questionnaire based on